The Effect of flaxseed on cervical ripening and delivery outcome in primiparous women: a randomized clinical trial - Zohre Ghorashi; Ahmad Reza Sayadi; Pouran Allahbakhshinasab (Mashhad University of Medical Sciences, 2024)
introduction: Chemical and herbal medicines are used to facilitate vaginal delivery and reduce cesarean section. Unripe cervix is associated with many complications. Since chemical drugs may be associated with maternal and fetal complications, the present study was performed with aim to determine the effect of flaxseed on cervical ripening and delivery outcome. Methods: This randomized clinical trial study was conducted in 2018-2021 on 120 primiparous women referred to a midwifery office in Rafsanjan city. The samples were randomly divided into intervention and control groups. Then, 28 packets of 10 gr of flaxseed powder were provided to the intervention group, so that from the 37th week of pregnancy until delivery, they eat one packet in a glass of warm water every morning as fasting. The control group received no intervention. The study tool was a demographic and obstetric information questionnaire, and the two groups were compared in terms of cervical ripening and maternal and neonatal outcomes. Data analysis was done using SPSS software (version 22) and independent t and chi-square statistical tests. P<0.05 was considered statistically significant. Results: At admission time, the two groups had statistically significant differences in cervical ripening, and it was higher in the intervention group (p=0.01). Also, the first stage duration of labor was shorter in the intervention group (p=0.03). The two groups had no statistically significant difference in terms of other delivery outcomes, including admission cause, induction and strengthening of labor pains, the second stage duration, fetal distress, meconium passing, type of delivery, first and fifth minute Apgar scores, and postpartum hemorrhage (p<0.05). Conclusion: The use of flaxseed increases the probability of cervical ripening and shortens the first stage and the course of childbirth.